The use of small stents to delay surgical intervention in very young children with critical congenital heart disease - Greig, Carrie Lee; Buys, D.G.; Brown, S.C.; Smit, F.E. (SA Heart Journal, 2017)
Introduction: Surgery in very young children with critical obstructive congenital heart disease has a high morbidity and mortality. The aim of this study was to determine whether the use of small stents is feasible and if it could delay surgery. Materials and methods: Nineteen children were included in a retrospective review spanning 7 years. Patients were included in circumstances where surgery needed to be delayed and the use of a small stent could alleviate the underlying obstruction. Results: All attempts at stenting were successful (100%). Indications were diverse and included: aortic obstruction (n=9), right ventricular outfl ow tract obstruction (n=3), systemic-to-pulmonary artery shunt occlusion (n=5), infradiaphragmatic pulmonary vein obstruction (n=1) and salvage of a discontinuous left pulmonary artery (n=1). Reasons patients were not fi t for surgical intervention included: low weight (n=4), poor general clinical condition (n=12), surgical technical diffi culty (n=2) and unavailability of a critical care bed (n=1). Median age and weight at procedure was 4.6 months (range: 0.1 - 18.3) and 4.5kg (range: 1.7 - 9.5), respectively. Pressure gradients and saturations showed signifi cant improvement post stenting. Periprocedural complications were few (n=3) and there were no fatalities. Last follow-up was at a median of 7.8 months (range: 0.1 -9.0) post initial procedure. Nine cases proceeded to corrective surgery. Surgery was delayed by a median 13.5 months (range: 0.3 - 69.0 months) and weight increased to a median of 10.3kg (p<0.001). Five cases demised at a median of 73 days (range: 1 - 422) post initial stent placement, most at home secondary to unknown causes. Four patients remain in follow-up. One patient was lost to follow-up. Conclusion: The placement of stents in small, ill children is feasible. It immediately relieves the obstruction and improves the general clinical condition. Surgery can be delayed for weeks or months, thus giving the opportunity for somatic growth.